Microcystin-LR removal from Microcystis aeruginosa using in natura sugarcane bagasse and activated carbon - Aline Rafaela de Almeida; Fernando Hermes Passig; Thomaz Aurélio Pagioro; Priscila Tiemi Higuti do Nascimento; Karina Querne de Carvalho2 (Revista Ambiente & Água, 2016)
Microcystin-LR is a type of toxin released by the Microcystis aeruginosa cyanobacteria found in water sources used for human consumption. It can cause illness and even death if not completely removed in conventional water treatment. The retention of this toxin is often accomplished by the adsorption process in activated carbon in water treatment plants. In this study, a comparison was made between the retention of microcystin-LR by activated carbon and by sugarcane bagasse in natura applied as a bio-adsorbent. Adsorption experiments were performed after the physical and chemical properties of the bio adsorbent and the activated carbon were characterized. The adsorption performance was evaluated by the toxin removal efficiency and the maximum adsorption capacity. Average removal efficiencies of the toxin resulted in 65.25; 41.74 and 11.75% for the activated carbon and 24.15; 18.92 and 12.27% for the sugarcane bagasse for concentrations of 2.36, 3.33 and 3.83 µg L-1, respectively. The bio adsorbent presented removal efficiency for the toxin similar to that observed in the activated carbon for the concentration of 3.83 µg L-1. Maximum adsorption capacity obtained with better linear adjustment to the Freundlich isotherm was 6,047.84 µg g-1 (toxin concentration of 3.83 µg L-1) for sugarcane bagasse and 338.61 µg g-1 (toxin concentration of 2.36 µg L-1) for activated carbon.